2014
DOI: 10.1057/sj.2014.5
|View full text |Cite
|
Sign up to set email alerts
|

Street robbery and public bus stops: A case study of activity nodes and situational risk

Abstract: Existing scholarship suggests that crime concentrates in close proximity to public bus stop locations. However, the importance of particular combinations of crime generators and attractors in the proximate environment around public bus stops has not been empirically documented. Drawing on previous environmental criminology research, the current study uses conjunctive analysis of case configurations to address questions about interpersonal violence around bus stops and other activity nodes in the proximate envi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(34 citation statements)
references
References 18 publications
1
30
0
3
Order By: Relevance
“…As previously noted in international literature, both external surroundings and internal station characteristics are important to the explanation of crime occurrences in the transit system environment (see, for instance, Ceccato et al, 2013;Hart and Miethe, 2014;Loukaitou-Sideris et al, 2002;Newton, 2014). In particular, our study found that stations' internal environmental features, such as the presence of CCTV and security guards, deter crime through formal social control.…”
Section: Discussion Of the Resultsmentioning
confidence: 94%
“…As previously noted in international literature, both external surroundings and internal station characteristics are important to the explanation of crime occurrences in the transit system environment (see, for instance, Ceccato et al, 2013;Hart and Miethe, 2014;Loukaitou-Sideris et al, 2002;Newton, 2014). In particular, our study found that stations' internal environmental features, such as the presence of CCTV and security guards, deter crime through formal social control.…”
Section: Discussion Of the Resultsmentioning
confidence: 94%
“…However, research has identified a higher likelihood of robbery victimization when a bus stop is located near an ATM compared to only an ATM, but a lower risk of robbery victimization when a bus stop is located near a bar compared to only a bar (Hart & Miethe, 2014). Robbers tend to commit robberies in places that fall within their routine travels and are close to their homes.…”
Section: Research On Transit Environments and Other Public Spacesmentioning
confidence: 99%
“…For instance, it is well established that a lack of a capable guardian is very often associated with more crime (Cohen and Felson 1979). More recently (Caplan et al 2011), the literature has listed five risk factors found to be correlated with crime, particularly those that are violent, these are: gang members (Kennedy et al 1996;Braga 2004); schools (Roncek and LoBosco 1983); public housing (Newman 1972;Eck 1987); the facilities of bars, clubs, fast food restaurants, and liquor stores Roncek and Maier 1991;Block and Block 1995;Brantingham and Brantingham 1995); and bus stops (Golledge and Stimson 1997;Loukaitou-sideris 1999;Roman 2005;Van Wilsem 2009;Yu 2009;Hart and Miethe 2014;Stucky and Smith 2014). Whilst most of these risk factors are too broad to be dealt with in one operation, they signal the direction in which to look for these antecedents of crime.…”
Section: Introduction Crime and Placementioning
confidence: 99%